The Impact of Running on Mental Health - A Literature Review - Łopińska, Joanna; Struzynska, Ewelina; Majchrzycka, Marta; Graczyk, Martyna; Majchrzak, Mateusz; Czapla, Natalia; Graczyk, Natalia; Ziółkowska, Weronika; Wisoky, Wiktor; Ignyś, Piotr (Quality in Sport, 2026)
This literature review explores the relationship between running and mental health, synthesizing findings from empirical studies, clinical trials, and meta-analyses. Running has been shown to improve mood, reduce symptoms of anxiety and depression, and enhance self-esteem, emotional stability, and overall psychological well-being. Biological mechanisms underlying these effects include increased neuroplasticity, improved mitochondrial function, and modulation of key neurotransmitters such as serotonin, dopamine, and endorphins. Psychological and social mechanisms such as enhanced self-efficacy, sense of agency, and social connectedness further contribute to long-term mental health benefits. Despite methodological and demographic limitations in current research, the evidence suggests that running is a practical, accessible, and low-cost approach to promoting mental well-being. Future directions include developing personalized exercise programs and integrating running into public health and therapeutic frameworks.